(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
Wireless sensor networks (WSNs) are made up of energy-constrained sensing devices capable of delivering the sensed data to one or more sinks. In a typical WSN scenario, the sink usually keeps stationary among the sensors that are static as well. The study and analysis of the performance of these networks is based on a variety of models that vary according to the network and the different factors that determine performance evaluation. The use of the Graph theory gives great flexibility in such cases, particularly when the complexity of the problem is increased using mobile sinks to achieve multiple objectives, including extending the life of the network. In addition, because of the importance of the management of energy consumption and its direct impact on the network lifetime prolonging, this research trend aims at proposing energy-efficient algorithm where the mobility of the sink is exploited for maximizing the lifetime of the network. It focused on suggestion and testing algorithm to move the sink based on the formulation of a graphical model takes into account the factors, which affect the movement of sink, and ensure the network lifetime prolonging. The implementation of the proposed algorithm have been tested for ZigBee based wireless sensors networks with a mobile sink through intensive simulations using NS-2 simulator. Where the results proved the feasibility of the mobile sink approach by demonstrating the improved network lifetime in several deployment scenarios. ﺗﺗﻛون ﺷبكات اﻟﺣﺳﺎﺳﺎت اﻟﻼﺳﻠﻛية (WSN) ﻣن أﺟﻬزة ﺗﺣﺳس ﻣﺣدودة اﻟطﺎﻗﺔ ﻗﺎدرة ﻋﻠﻰ إيصال اﻟﺑياﻧﺎت اﻟﻣﺣﺳوﺳﺔ إﻟﻰ واﺣد أو أﻛﺛر ﻣن اﻟﻣﻧﺎﻓذ. يكون اﻟﻣﻧسق ﺛﺎﺑﺗاً ﻋﺎدة ﻓﻲ ﺳﯾﻧﺎريو WSN ﻧﻣوذﺟﻲ ﺑﯾن أﺟﻬزة ﺗﺣﺳس ثابتة كذلك. تستند الدراسة والتحليل لأداء هذه الشبكات إلى مجموعة متنوعة من النماذج التي تختلف وفقاً للشبكة والعوامل المختلفة التي تحدّد تقييم الأداء. يعطي استخدام نظرية البيان مرونة كبيرة في مثل هذه الحالات، لاسيما عندما يتم زيادة تعقيد المشكلة باستخدام المنسقات المتنقلة لتحقيق أهداف متنوعة، بما في ذلك إطالة حياة الشبكة. إضافةً لذلك ونظراً لأهمية استهلاك الطاقة وتأثيرها المباشر على إطالة عمر الشبكة، يتجه هذا البحث إلى اقتراح خوارزمية فعالة من حيث الطاقة حيث يتم استغلال حركة المنسق لتحقيق أطول عمر للشبكة، وركّزت الدراسة على اقتراح واختبار خوارزمية لنقل المنسق على أساس صياغة نموذج بياني يأخذ بالحسبان العوامل التي تؤثر على حركة المنسق، بما يضمن إطالة عمر الشبكة. وﻗد ﺗم اﺧﺗبار ﺗﻧﻔﯾذ الخوارزﻣية اﻟﻣﻘﺗرﺣﺔ ﻣن أﺟﻞ ﺷبكة WSN ﺗﺳﺗﺧدم ZigBee ﻟﺗوﺻﯾﻞ أﺟﻬزة ﺷبكة اﻟﺣﺳﺎﺳﺎت اﻟﻼﺳﻠﻛية ﻣﻊ اﻟﻣﻧﻔذ اﻟﻣﺗﺣرك وذﻟك ﻣن ﺧﻼل اﻟﻣﺣﺎﻛﺎة باﺳﺗﺧدام اﻟﻣﺣﺎﻛﻲ NS-2 . ﺣﯾث أﺛﺑﺗت اﻟﻧﺗﺎﺋﺞ ﺟدوى طريقة ﺗﺣريك اﻟﻣﻧﻔذ ﻣن ﺧﻼل إظﻬﺎر اﻟزيادة ﻓﻲ ﻋﻣر اﻟﺷبكة ﻓﻲ اﻟﻌدﯾد ﻣن ﺳﯾﻧﺎريوﻫﺎت ﻧﺷر اﻟﺷبكة